The Role of Transcriptional Factor Brachyury on Cell Cycle Regulation in Non-small Cell Lung Cancer - Xu, Jingyi; Chen, Ming; Wu, Yinghui; Zhang, Hong; Zhou, Jundong; Wang, Donglai; Zou, Tianming; Shen, Jun (Frontiers in Oncology, 2020)
Lung cancer is the leading cause of cancer-related death,and non-small cell lung cancer (NSCLC) accounts for almost 80-85% of all lung cancer cases.The transcriptional factor brachyury has been verified to promote tumor cells migrate, invade and metastasis in various types of tumors, whereas divergent roles of brachyury on cell proliferation have been reported in several types of tumor cells. In this study, we attempted to explore the effect of brachyury on the cell cycle progression and proliferation capability of NSCLC cells. Firstly, we performed RNA-sequence and ChIP-sequence to explore novel downstream pathways regulating by brachyury. Cell proliferation and colony formation assays were utilized to detect the effect of brachyury on the proliferation ability of two types of lung NSCLC cells: H460 and Calu-1, which represent different brachyury expression levels. Following Cell cycle and cell apoptosis assays were used to investigate the mechanism by which brachyury promotes NSCLC grow and progression. RNA-sequence and ChIP-sequence (ChIP-seq) showed that one of the vital downstream pathways regulated by brachyury involves in cell cycle progression. Through cell proliferation assays and colony formation assays, we found that inhibition of brachyury could decrease the capability of proliferation in H460 cells. We also found that brachyury overexpression could prevent the transition from G0/G1 to S phase in Calu-1 cells, and brachyury knockdown could decrease the transition of G2/M phase in H460 cells. The cell apoptosis assays showed that inhibition of brachyury could promote apoptosis in H460 cells. In this study we demonstrate that brachyury and downstream target genes together involve in tumor cell cycle regulation by inducing accelerated transition through G2/M, promote tumor cell proliferation and inhibit apoptosis in lung NSCLC H460 cells. Targeting brachyury expression could be developed into a promising avenue for the prevention of lung cancer progression.